HOW TO STIMULATE STUDENTS TO REGULAR WORK DURING THE SEMESTER - Mikhail A. Prikhodovsky (Moscow Polytechnic University, 2022)
We consider a set of specific incentives to encourage regular, systematic learning by students an educational material during the semester. Among them are the following: more liberal, friendly atmosphere, possibility of pre-term examination, taking into account the results of student's work during a semester, invariability of the requirements, feedback between lecturer and student.